2013
DOI: 10.1016/j.cell.2013.07.029
|View full text |Cite
|
Sign up to set email alerts
|

A Gain-of-Function Mutation in DHT Synthesis in Castration-Resistant Prostate Cancer

Abstract: Summary Growth of prostate cancer cells is dependent upon androgen stimulation of the androgen receptor (AR). Dihydrotestosterone (DHT), the most potent androgen, is usually synthesized in the prostate from testosterone secreted by the testis. Following chemical or surgical castration, prostate cancers usually shrink owing to testosterone deprivation. However, tumors often recur, forming castration-resistant prostate cancer (CRPC). Here, we show that CRPC sometimes expresses a gain-of-stability mutation leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
293
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 273 publications
(308 citation statements)
references
References 39 publications
9
293
1
3
Order By: Relevance
“…For example, androgen receptor selectively upregulates M-phase cell cycle genes to promote CRPC (67). Interestingly, a recent study found that a gain-of-function mutation in dihydrotestosterone (the most potent androgen) synthesis partially accounts for castration resistance (68). However, some other studies have challenged the androgen receptor-dependent mechanism, as castration induces the activation of many kinases (69) and increases the expression of antiapoptotic genes independently of the androgen receptor (70).…”
Section: Discussionmentioning
confidence: 96%
“…For example, androgen receptor selectively upregulates M-phase cell cycle genes to promote CRPC (67). Interestingly, a recent study found that a gain-of-function mutation in dihydrotestosterone (the most potent androgen) synthesis partially accounts for castration resistance (68). However, some other studies have challenged the androgen receptor-dependent mechanism, as castration induces the activation of many kinases (69) and increases the expression of antiapoptotic genes independently of the androgen receptor (70).…”
Section: Discussionmentioning
confidence: 96%
“…Shared resistance mechanisms involve alternative strategies to activate the AR, such as intratumor steroid biosynthesis, 57 activation of the glucocorticoid receptor 58 and emergence of an AR splice variant, such as ARV7, 59 as well as activation of non-AR survival pathways. With regard to the interaction between ASIs and docetaxel, Schweizer et al reported, in the retrospective study of 119 mCRPC patients, shorter PFS in patients (n = 24) who were treated with abiraterone followed by docetaxel compared with patients (n = 95) treated with only docetaxel (PFS of 7.6 months in docetaxel and 4.4 months in abiraterone followed by docetaxel, P = 0.003), implying the cross-resistance between ASIs and docetaxel.…”
Section: Cross-resistance Between Classes Of Agentsmentioning
confidence: 99%
“…1). Expression of the 1245C SNP results in increased HSD3B1 protein levels via inhibition of ubiquitin-mediated degradation and subsequently a greater flux toward DHT synthesis (Chang et al 2013). Heterozygous HSD3B1 variant (1245C) allele has been associated with a shorter time to CRPC in a Chinese cohort of 108 patients where the heterozygote prevalence was 17% (Wu et al 2015).…”
Section: Genomic Alterations Implicating Sex Steroids In Prostate Canmentioning
confidence: 99%